Genetic Variants in the ST6GAL1 Gene Are Associated with Thyroglobulin Plasma Level in Healthy Individuals - Matana, Antonela; Popović, Marijana; Boutin, Thibaud; Torlak, Vesela; Brdar, Dubravka; Gunjača, Ivana; Kolčić, Ivana; Boraska Perica, Vesna; Punda, Ante; Rudan, Igor; Polašek, Ozren; Barbalić, Maja; et al. (Thyroid (New York, N.Y.), 2019)
Thyroglobulin (Tg) is a 660 kDa iodoglycoprotein that serves as a scaffold for thyroid hormone synthesis. Although a twin study showed that variability of serum Tg levels has a substantial genetic basis, no genome-wide association study (GWAS) of serum/plasma Tg levels has been performed to date. The aim of this study was to identify genetic variants associated with plasma Tg levels among healthy individuals. A GWAS was conducted on two Croatian cohorts, and a combined analysis was performed. The analyses included 1094 individuals. A total of 7,597,379 variants, imputed using the 1000 Genomes reference panel, were analyzed for association. GWAS was performed under an additive model, controlling for age, sex, and relatedness within each data set. Combined analysis was conducted using the inverse-variance fixed-effects method. Sixteen variants located on chromosome 3, within the gene, reached genome-wide significance. The lead SNP was rs4012172 ( \documentclass{aastex}\usepackage{amsbsy}\usepackage{amsfonts}\usepackage{amssymb}\usepackage{bm}\usepackage{mathrsfs}\usepackage{pifont}\usepackage{stmaryrd}\usepackage{textcomp}\usepackage{portland, xspace}\usepackage{amsmath, amsxtra}\usepackage{upgreek}\pagestyle{empty}\DeclareMathSizes{10}{9}{7}{6}\begin{document} $$p = 1.29 × {10^{ - 10}}$$ \end{document} ), which explained 3.19% of the variance in Tg levels. belongs to the sialyltransferase protein family, which has a fundamental role in the synthesis of specific sialylated structures on various glycoproteins, including Tg. It is known that only immature Tg (poorly sialylated or desialylated) can be transferred to the bloodstream. A highly biologically plausible locus was identified that could have a role in the regulation of plasma Tg levels in healthy individuals.